The Idea of Phenomenology - Husserl, Edmund. author. aut Link
XXIV, 60 p.
Keywords: This translation is concluded in our Readings in Twentieth Century Philosophy, (N. Y. , The Free Press of Glencoe, Inc. , 1963). We owe thanks to Professors W. D. Falk and William Hughes for helping us with the translation. We also owe thanks to Professor Herbert Spiegelberg, Dr. Walter Biemel and the Husser! Archives at Louvain for checking it and we are especially indebted to Professor Dorion Cairns, many of whose suggestions we incorporated in the final draft. WILLIAM P. ALSTON GEORGE NAKHNIKIAN January 1964 CONTENTS V Preface Introduction IX The train of thoughts in the lectures I Lecture I 13 Lecture II 22 Lecture III 33 Lecture IV 43 Lecture V 52 INTRODUCTION From April 26 to May 2, 1907, Husserl delivered five lectures in Gottingen. They introduce the main ideas of his later pheno menology, the one that goes beyond the phenomenology of the Logische Untersuchungen. These lectures and Husserl's summary of them entitled "The Train of Thoughts in the Lectures" were edited by Dr. Walter Biemel and first published in 1950 under the 1 title Die Idee der Phiinomenologie. Husserl wrote the summary on the night of the last lecture, not for formal delivery but for his own use. This accounts for the fact that the summary contains incomplete sentences. There are some discrepancies between Lecture V and the corresponding passages in the summary. We may suppose that the passages in the summary are a closer approximation to what Husserl wanted to say.